DETERMINASI KESULITAN KEUANGAN DAN DAMPAKNYA TERHADAP MANAJEMEN LABA: BUKTI DARI PERUSAHAAN INFRASTRUKTUR DAN TRANSPORTASI INDONESIA - Robben Alessandro Marpaung; Sekar Mayangsari (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
The pecuniary perturbations experienced by corporations harbor the potential to unsettle operational equanimity and imperil commercial perpetuity, particularly within capital-intensive dominions such as infrastructure and transportation. On this rationale, the present inquiry is orchestrated to dissect the contribution of endogenous determinants specifically profitability, leverage, and liquidity in sculpting corporate financial distress susceptibility. The research corpus comprises entities in the infrastructure and transportation sectors enlisted on the Indonesia Stock Exchange over the 2022–2024 span. A quantitative paradigm is deployed herein, employing panel data regression techniques to elucidate the interplay among the probed variables. Empirical exegesis reveals that profitability and liquidity correlate with abatement of financial distress, intimating that a firm’s adeptness in generating earnings while concurrently safeguarding sufficiency of current assets functions as a pivotal mechanism in mitigating fiscal strain. Contrariwise, leverage exhibits no discernible influence on financial distress, suggesting that debt-based capital composition does not per se prescribe the magnitude of corporate financial tribulation absent prudent stewardship of obligations and cash flows. Collectively, these findings underscore that fortification of internal fiscal performance constitutes a sine qua non for preserving corporate stability and perpetuity.